Application of pumpkin flour to the diet of Barramundi Lates calcarifer fingerling - Riska Z. Yanti; Zainal A. Muchlisin; Abdullah A. Muhammadar; Nur Fadli (Depik, 2022)
BarramundiLates calcariferis a high economic value fish in Indonesia and Southeast Asia countries. However, the aquaculture system still experiences problems, including the high cost of production, specifically from feed, which is due to its relatively slow growth and low digestibility. Therefore, this study aims to determine alternative ingredients that can be used in the fish diet to improve feed utilization and growth performance using pumpkin flourCucurbita moschata. A completely randomized design (CRD) with 6 treatments and 3 replications was adopted in this study. The tested diet was (A) diet without pumpkin flour (control), (B) with 5% (C) 10% (D) 15% (E) 20%, and (F) 25%. The size of the Barramundi samples was 3-4 cm on average and the body weight was 1-3 g at the stocking density of 15 fish/container. The fish fed as much as 10% body weight daily, which is divided into 2 times, namely 08.00 AM and 4.00 PM for 60 days. The results showed that the addition of pumpkin flour had a significant effect on weight gain, daily and specific growth rate, survival, feed efficiency, conversion ratio, and carcass protein (P0.05). The diet with 5% pumpkin flour gave the best results over other treatments, with an average weight gain of 0.761 g, feed conversion of 1.578, feed efficiency of 63.455%, and a daily and specific growth rate of 0.012 g and 0.738%, respectively, The highest carcass protein content was found in the control treatment with a value of 18.210%, which was not significantly different from the 5% pumpkin flour treatment. Therefore, it is concluded that pumpkin flour can be added to the Barramundi diet as much as 5%.Keywords:Barramundi, Snapper, pumpkin,feed utilization